3(x+0.9)=5(x-1.7)解方程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 13:25:23
3(x+0.9)=5(x-1.7)解方程3(x+0.9)=5(x-1.7)解方程3(x+0.9)=5(x-1.7)解方程3X+2.7=5X-8.53X-5X=-8.5-2.7-2X=-11.22X=1
3(x+0.9)=5(x-1.7)解方程
3(x+0.9)=5(x-1.7)
解方程
3(x+0.9)=5(x-1.7)解方程
3X+2.7=5X-8.5
3X-5X=-8.5-2.7
-2X=-11.2
2X=11.2
X=5.6
3(x+0.9)=5(x-1.7)解方程
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
3x-x=0.9 解方程
x+3=5x 解方程
解方程:5x=3x
解方程:解方程:5+3x=17.6-x
解方程:1.7x+5=3x+5 2.3x=-6x
解方程:(x+10)+(x-15)=280-x x+15=3*(109-x) 5(3x-1.4)=2(6x-0.5) 3(x+0.9)=5(x-1.7) 13x-4(...解方程:(x+10)+(x-15)=280-xx+15=3*(109-x) 5(3x-1.4)=2(6x-0.5) 3(x+0.9)=5(x-1.7)13x-4(2x+5)=17(x-2)-4(2x-1)
解方程 x(2x-4)+3x(x-1)=5x(x-3)+8
解方程 3x/x×x-1+x×x-1/3x=5/2
解方程(x-3/x)-(3-x/x+1)=5x-15/2x+2
解方程:x(3x-4)+2x(x+7)=5x(x-7)+90
解方程:(x-2)(x^2-6x-9)=x(x-5)(x-3)
解方程:2(X-3)(X+5)=X平方+(X+2)(X-2)+(X+7)
3x-5x=5+x解方程
4x-3(20-x)=5x解方程
解方程3(x-2)=5x(x-2)
解方程:(2-x)(3-x)(5-x)=51